MASLOW'S THEORY STUDY: EMPLOYEE WORK MOTIVATION APPROACH - Umi Nurjanah; Enjang Suherman (Enrichment : Journal of Management, 2022)
Various kinds of work motivation theories are contained in organizational behavior, including Maslow's theory of needs. Although Maslow's theory is old, it is still used in modern organizations. The employees work motivation in this research, was studied based on Maslow's hierarchy of needs theory approach consisting of physical needs, security needs, social needs, esteem needs, and actualization needs. This study aims to describe quantitatively the conditions of employee motivation using Maslow's needs approach. The research design uses a quantitative descriptive approach. The sample of this study amounted to 158 respondents from a population of 262 employees. Data collection methods in the form of questionnaires, surveys, and interviews. While the research instrument used a questionnaire with a Likert scale. And data analysis using scale range analysis. The results showed that work motivation was based on physiological needs, security needs, social needs, esteem needs, and self-actualization needs at high motivation levels.